إشكالية إدراج الشعر في السردية الروائية: دراسة تحليلية وصفية: The Challenge of Integrating Poetry into Novel: An Analytical and Descriptive Study - Hilal, براء خالد هلال (الدراسات الإسلامية, 2025)
Integrating poetic foundations within narrative fiction represents an exclusive literary phenomenon, particularly in Arabic literature, where including poetry in novels remains relatively infrequent. Novelists often introduce poetic characters into their stories, necessitating the incorporation of poetic texts within the narrative framework. While this practice enriches the narrative and enhances dialogue, it presents a significant challenge, as novelists are primarily storytellers rather than poets. This study explores the early stages of Arabic novels, where strict literary categorisation prevailed and examines how the works of prominent writers such as Ali al-Jarim and Ali Ahmad Bakathir pioneered the blending of poetry and prose in the twentieth century. Their contributions paved the way for subsequent novelists, leading to a convergence of poetic and narrative forms in contemporary literature. This research employs an analytical-descriptive approach to investigate the complexities of this literary overlap, focusing on the thematic and stylistic intersections between poetry and prose. Both forms share the capacity to address profound themes such as love, death, and human existence, utilising poetic language and figurative imagery to convey philosophical, social, and political messages. The study also highlights the challenges confronted by novelists in maintaining literary consistency when integrating poetry into narrative fiction. By examining the relationship between poetic and novelistic elements, this research contributes to a deeper understanding of literary genres in the twentieth century and the evolving dynamics of Arabic literature.